FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN RETENSIO PLASENTA - Yani; Ellina; Yulizar; Eka Rahmawati (Jurnal Kesehatan dan Pembangunan, 2023)
Bleeding is the number one cause of maternal death 40-60% of maternal deaths in Indonesia. This study aims to determine the factors associated with the incidence of retained placenta in the Prabumulih Regional General Hospital in 2020. This type of research is quantitative using an analytical survey method. through a cross sectional approach. The sample of this study was all maternity mothers who were treated at the Prabumulih Regional General Hospital in 2020 totaling 678 using random techniques, using simple random sampling (simple random sampling) with a sample of 88 respondents. This study uses secondary data, namely data taken from medical record observations using a check list. The results of the univariate analysis showed that of the 88 respondents who had retained placenta, 43 people (48.9%) were smaller than those who did not experience retained placenta, as many as 45 people (51.1%). From the results of bivariate analysis, P Value = 0.047 < 0.05, this indicates that there is a significant relationship between age and the incidence of retained placenta, P Value = 0.029 < 0.05, there is a significant relationship between parity and retained placenta, obtained P Value = 0.006 < 0 0.05 there is a relationship between history of abortion and retained placenta and obtained P Value = 0.000 <0.05, this indicates that there is a significant relationship between history of cesarean section and the incidence of retained placenta.